Teresina: entre a vanguarda e as cousas pretéritas (1852 ao primeiro decênio do século XX) - Silva, Victor Marcelo Pires Gonçalves da (2020)
The socio-cultural universe of Teresina presents itself as a plausible proposal in the complex and diverse field that has come to be called by some historians the New Cultural History, providing interpretations of the meanings given to the world, expressed in words, images, practices and speeches. This study certainly tries to highlight some aspects and features that constitute the culture, in order to contribute to the understanding of the multi-faceted scenario from Teresina. And, thereby, found an analysis on the past residues that constitute cultural aspects of ruptures and permanencies in the city since its foundation, from the middle of the 19th century to the first decade of the 20th century. These trails are investigated in sociability, presenting as in a dynamic and fluid performance. Thus, this analysis starts from the rationality established by the modernizing project to represent progress, growth, development, transformation and forefront over representations such as isolation, poverty, backwardness, inertia of the sertanejo context, justifying the foundation of the new capital of the province of Piauí opposite to the cultural traditions resistant to the logic of this dynamism. This reveals the complexity of the cultural agreements in Teresina as a hybrid space of different possibilities, representations and identifications